The Determinants of Corporate Risk in Emerging Markets : An Option-Adjusted Spread Analysis - Cavallo, Eduardo (IMF Working Papers; Working Paper, 2007)
This study explores the determinants of corporate bond spreads in emerging markets economies. Using a largely unexploited dataset, the paper finds that corporate bond spreads are determined by firm-specific variables, bond characteristics, macroeconomic conditions, sovereign risk, and global factors. A variance decomposition analysis shows that firm-level characteristics account for the larger share of the variance. In addition, the paper finds two asymmetries. The first is in line with the sovereign ceiling "lite" hypothesis which states that the transfer of risk from the sovereign to the private sector is less than 1 to 1. The second is consistent with the popular notion that panics are common in emerging markets where investors are less informed and more prone to herding.